2017
DOI: 10.1002/epi4.12037
|View full text |Cite
|
Sign up to set email alerts
|

EFHC1 mutation in Indian juvenile myoclonic epilepsy patient

Abstract: SummaryObjectiveJuvenile myoclonic epilepsy (JME) is the most common form of idiopathic generalized epilepsies (IGEs) and is genetically heterogeneous. Mutations in EFHC1 cause JME. Because about 2 million people in India are affected by JME alone, we investigated the prevalence of mutations in the EFHC1 gene in the Indian population with JME. We studied 63 patients with JME and 80 healthy controls.MethodsClinical identification of JME was evaluated using established criteria. Following clinical evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Later on, new heterozygous mutations in EFHC1 were described in other Mexican, Honduras, and Japanese families but also in 3 unrelated Italian families and in 5 patients from Austria (Stogmann et al, 2006; Annesi et al, 2007; Medina et al, 2008; Jara-Prado et al, 2012). Recently two studies performed in India described 5 missense mutations in six independent families and 13 mutations in 28 patients (Raju et al, 2017; Thounaojam et al, 2017). While pathogenic variants of EFHC1 are present in 3% of Japanese JME patients, in 7 to 9% in JME patients from Mexico and Honduras and in 5% of JME patients from India, pathogenic variants of EFHC1 may be extremely rare in JME patients from Germany while possibly absent in the Dutch, Swedish, and United Kingdom populations.…”
Section: Genes Associated With Jme and Their Cellular Rolementioning
confidence: 99%
“…Later on, new heterozygous mutations in EFHC1 were described in other Mexican, Honduras, and Japanese families but also in 3 unrelated Italian families and in 5 patients from Austria (Stogmann et al, 2006; Annesi et al, 2007; Medina et al, 2008; Jara-Prado et al, 2012). Recently two studies performed in India described 5 missense mutations in six independent families and 13 mutations in 28 patients (Raju et al, 2017; Thounaojam et al, 2017). While pathogenic variants of EFHC1 are present in 3% of Japanese JME patients, in 7 to 9% in JME patients from Mexico and Honduras and in 5% of JME patients from India, pathogenic variants of EFHC1 may be extremely rare in JME patients from Germany while possibly absent in the Dutch, Swedish, and United Kingdom populations.…”
Section: Genes Associated With Jme and Their Cellular Rolementioning
confidence: 99%
“…We originally and mistakenly reported that myoclonin1 is expressed in neurons of mouse brain (Suzuki et al, 2004), but our subsequent studies using Efhc1 -/mouse and a newly-developed mouse monoclonal antibody for myoclonin1 (6A3-mAb) revealed that myoclonin1 is actually not expressed in neurons but dominantly expressed in choroid plexus at embryonic stages, and at motile cilia of ependymal cells, tracheal motile cilia, and sperm flagella at postnatal stages Suzuki et al, 2009;Suzuki et al, 2020). EFHC1 heterozygous missense mutations in patients with epilepsies including JME have been repeatedly reported by us and many other groups (Suzuki et al, 2004;Ma et al, 2006;Stogmann et al, 2006;Annesi et al, 2007;Medina et al, 2008;Jara-Prado et al, 2012;Coll et al, 2016;Bailey et al, 2017;Raju et al, 2017;Thounaojam et al, 2017;Wang et al, 2017;Lin et al, 2023). A missense mutation in EFHC1 has also been identified homozygously in patients with intractable epilepsy of infancy (Berger et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…The mutations that have been reported in these genes were private mutations, only found in single families and typically of de novo origin, that are not spotted in biological parents. Importantly, these de novo mutations (DNMs) were not detected in other family-based association studies for JME in the same or different ethnicities [ 16 ]. Consequently, mutations in genes coding for ion channel proteins cannot be accounted as the common cause of JME.…”
Section: Introductionmentioning
confidence: 99%